A Parametric Investigation Into the Effect of Low Induction Rotor (LIR) Wind Turbines on the Levelised Cost of Electricity for a 1 GW Offshore Wind Farm in a North Sea Wind Climate. (September 2016) - Quinn, R.; Schepers, G.; Bulder, B.
Abstract: In this report, the details of an investigation into the effect of low induction rotor (LIR) wind turbines on the Levelised Cost of Electricity (LCoE) in a 1GW offshore wind farm is outlined. The 10 MW INNWIND.EU conventional wind turbine and its low induction variant, the 10 MW AVATAR wind turbine, are considered in a variety of 10x10 layout configurations. The Annual Energy Production (AEP) and cost of electrical infrastructure were determined using two in-house ECN software tools, namely FarmFlow and EEFarm II. Combining this information with a generalised cost model, the LCoE from these layouts were determined. The optimum LCoE for the AVATAR wind farm was determined to be 92.15 e/MWh while for the INNWIND.EU wind farm it was 93.85 e/MWh. Although the low induction wind farm offered a marginally lower LCoE, it should not be considered as definitive due to simple nature of the cost model used. The results do indicate that the AVATAR wind farms require less space to achieve this similar cost performace, with a higher optimal wind farm power density (WFPD) of 3.7 MW/km2 compared to 3 MW/km2 for the INNWIND.EU based wind farm.